Nicholas Milton : Conductor. - Milton, Nicholas (Surry Hills, N.S.W. : Nicholas Milton, 2009)
"Nicholas Milton has established an outstanding reputation for his charismatic stage presence and powerful interpretations of an extensive repertoire spanning both concert and opera. Renowned for his dynamic conducting style and compelling musical integrity, he continues to attract international attention as one of the most outstanding Australian conductors working today."
Title from title screen (viewed on 28 April 2016)
Mode of access: Available Online. Address as at 27/05/2016
Selected for archiving
Keywords: Milton, Nicholas; Conductors (Music) -- Australia; Australian